Focal Therapy for Prostate Cancer: Complications and Their Treatment - Rakauskas, Arnas; Marra, Giancarlo; Heidegger, Isabel; Kasivisvanathan, Veeru; Kretschmer, Alexander; Zattoni, Fabio; Preisser, Felix; Tilki, Derya; Tsaur, Igor; van den Bergh, Roderick; Kesch, Claudia; Ceci, Francesco; et al. (Frontiers in Surgery, 2021)
Focal therapy is a modern alternative to selectively treat a specific part of the prostate harbouring clinically significant disease while preserving the rest of the gland. The aim of this therapeutic approach is to retain the oncological benefit of active treatment and to minimise the side-effects of common radical treatments. The oncological effectiveness of focal therapy is yet to be proven in long-term robust trials. In contrast, the toxicity profile is well established in randomized controlled trials and multiple robust prospective cohort studies. This narrative review summarizes the relevant evidence on complications and their management after focal therapy. When compared to whole gland treatments, focal therapy provides a substantial benefit in terms of adverse events reduction and preservation of genito-urinary function. The most common complications occur in the peri-operative period. Urinary tract infection and acute urinary retention can occur in up to 17% of patients, while dysuria and haematuria are more common. Urinary incontinence following focal therapy is very rare (0-5%), and the vast majority of patients recover in few weeks. Erectile dysfunction can occur after focal therapy in 0-46%: the baseline function and the ablation template are the most important factors predicting post-operative erectile dysfunction. Focal therapy in the salvage setting after external beam radiotherapy has a significantly higher rate of complications. Up to one man in ten will present a severe complication.